"We're not short of people telling us what the problems are. We're short of people telling us what to do": An appraisal of public policy and mental health - Wilson Sarah; McCollam Allyson; Platt Stephen; Petticrew Mark; Thomas Sian (BMC, 2008)
Abstract Background There is sustained interest in public health circles in assessing the effects of policies on health and health inequalities. We report on the theory, methods and findings of a project which involved an appraisal of current Scottish policy with respect to its potential impacts on mental health and wellbeing. Methods We developed a method of assessing the degree of alignment between Government policies and the 'evidence base', involving: reviewing theoretical frameworks; analysis of policy documents, and nineteen in-depth interviews with policymakers which explored influences on, and barriers to cross-cutting policymaking and the use of research evidence in decisionmaking. Results Most policy documents did not refer to mental health; however most referred indirectly to the determinants of mental health and well-being. Unsurprisingly research evidence was rarely cited; this was more common in health policy documents. The interviews highlighted the barriers to intersectoral policy making, and pointed to the relative value of qualitative and quantitative research, as well as to the imbalance of evidence between "what is known" and "what is to be done". Conclusion Healthy public policy depends on effective intersectoral working between government departments, along with better use of research evidence to identify policy impacts. This study identified barriers to both these. We also demonstrated an approach to rapidly appraising the mental health effects of mainly non-health sector policies, drawing on theoretical understandings of mental health and its determinants, research evidence and policy documents. In the case of the social determinants of health, we conclude that an evidence-based approach to policymaking and to policy appraisal requires drawing strongly upon existing theoretical frameworks, as well as upon research evidence, but that there are significant practical barriers and disincentives.